Polypropylene, polyester or polytetrafluoroethylene - is there an ideal material for mesh augmentation at the esophageal hiatus?: Results from an experimental study in a porcine model - Müller, Beat P.; Senft, Jonas; Lasitschka, Felix; Billeter, Adrian; Bruckner, Thomas; Kenngott, Hannes Götz; Fischer, Lars; Gehrig, Tobias (Hernia, 2014)
Purpose: Knowledge about the influence of underlying biomaterial on behavior of surgical meshes at the esophageal hiatus is rare, but essential for safe and effective hiatal hernia surgery. This study aimed to characterize the influence of polymer material on mesh behavior at the hiatus. Methods: 24 pigs in three groups of eight underwent implantation of either polypropylene (PP), polyester (PET) or polytetrafluoroethylene (PTFE) mesh placed circularly at the esophageal hiatus. After 8 weeks, necropsy and measurements were performed evaluating mesh deformation, adhesion formation, fixation of the esophagogastric junction and mesh position. Foreign body reaction was assessed by mononuclear cell count and immunostaining of Ki-67. Tissue integration was evaluated by immunostaining of type I and type III collagen fibers. Results: Mesh shrinkage was the highest for PTFE, lower for PP and the lowest for PET (34.9 vs. 19.8 vs. 12.1 %; p = 0.002). Mesh aperture for the esophagus showed an enlargement within all groups, which was highest for PTFE compared to PP and PET (100.8 vs. 47.0 vs. 35.9 %; p = 0.001). The adhesion score was highest for PP, lower for PTFE and the lowest for PET (11.0 vs. 9.5 vs. 5.0; p = 0.001) and correlated positively with the score of esophagogastric fixation (r s = 0.784, p < 0.001). No mesh migration, erosion or stenosis of the esophagus occurred. Evaluation of foreign body reaction and tissue integration showed no significant differences. Conclusions: In this experimental setting, PP-meshes showed the most appropriate characteristics for augmentation at the hiatus. Due to solid fixation of the esophagogastric junction and low shrinkage tendency, PP-meshes may be effective in preventing hiatal hernia recurrence. The use of PTFE-mesh at the hiatus may be disadvantageous due to high shrinkage rates and correlating enlargement of the aperture for the esophagus.